THE IMPORTANCE OF CONTINUING EDUCATION IN GENERAL DIDACTICS FOR PEDAGOGY TEACHERS: CHALLENGES, STRATEGIES AND IMPACTS ON EDUCATIONAL QUALITY - Domingos de Lira, Bruno (Revista Gênero e Interdisciplinaridade, 2025)
This article discusses the relevance of continuing education for teachers in the Pedagogy course, with a special focus on the discipline of General Didactics, as an effective strategy to improve educational quality. Continuing education is essential for teachers to stay up to date with the constant transformations in the field of education, ensuring the implementation of innovative and effective pedagogical practices. However, this journey of professional development is accompanied by significant challenges, such as the need for constant updating of pedagogical methods and limited resources. In this study, we analyze several strategies and methodologies that can be implemented to overcome these difficulties, highlighting the use of educational technologies and innovative approaches. Furthermore, we investigate how these practices directly impact the pedagogical practice of teachers and the academic results of students, providing a practical view through case studies. Existing policies and programs to support continuing education are also examined, offering constructive criticism and suggestions for improvements to maximize their effectiveness. Finally, this article proposes a set of recommendations for the future, with the aim of improving continuing education programs and, consequently, promoting quality and sustainable education.